Rationale and early clinical data on IL-17 blockade in psoriasis. (July 2013) - Nwe, Steven M; Champlain, Amanda H; Gordon, Kenneth B
Psoriasis vulgaris is a chronic, immune-mediated, inflammatory disease that affects between 2 and 3% of the US population. Often severely physically and emotionally debilitating, psoriasis has driven investigators to strive to better characterize its complex immune pathogenesis. Some of the most promising and exciting advances have occurred in the last decade with recognition of the IL-23/Th17 pathway in disease initiation, progression and maintenance. Biologic therapies targeting various points in the pathway have met with success, prompting the study of the safety and efficacy of IL-17 blockade for moderate-to-severe plaque psoriasis. This article will review the rationale and early clinical data on IL-17 blockade in psoriasis.